دور الصكوك الإسلامية في تمويل المشاريع الاستثمارية - سالمي، رشيد; عزي، هاجر Ezzi, Hajar (مركز البحث وتطوير الموارد البشرية رماح وجامعة العلوم الإسلامية العالمية, 2018)
تهدف هذه الدراسة إلى بيان وتوضيح دور الصكوك الإسلامية في تمويل المشاريع الكبرى، وذلك من خلال الصيغ والأدوات الحديثة التي تستخدمها. وللوصول إلى الهدف تحاول الدراسة توضيح مفهوم الصكوك الإسلامية وضوابطها الشرعية، ومدى إمكانية تطبيقها في العديد من الدول بما يعزز من دورها الاقتصادي والتنموي. وقد خلصت الدراسة إلى أن للصكوك الإسلامية دورا هاما في تمويل المشاريع التنموية، وقد نجحت كبديل للتمويل التقليدي في تمويل العديد من المشروعات الوطنية ومشاريع البنية التحتية دونما عبء على الميزانية العامة أو التوجه إلى المديونية.
This study aims to clarify the role of Islamic instruments in financing the big projects through using the new kinds of instruments. To reach the main purpose of this study, researcher tries to identify the concept of Islamic instruments and its controls in Islam. Also the application possibility in many countries to build up its economic and developmental role. The study concluded that Islamic instruments play an important role in the financing of development project. It is the financial alternative to the traditional financing according to its role especially in many national and infrastructural projects in isolation of public budget and Indebtedness.
Keywords: الصكوك الإسلامية -- التمويل الإسلامي -- المشاريع الاستثمارية -- التنمية الاقتصادية